Pengaruh Pemahaman Konsep dan Motivasi Belajar terhadap Prestasi Belajar Siswa - Ai Dini Patmawati (Journal on Education, 2025)
The objectives to be achieved in this study are to determine 1). The effect of conceptual understanding and learning motivation together on the science learning achievement of junior high school students in Sodonghilir District, Tasikmalaya Regency; 2). The effect of conceptual understanding on the science learning achievement of junior high school students in Sodonghilir District, Tasikmalaya Regency; 3). The effect of learning motivation on the science learning achievement of junior high school students in Sodonghilir District, Tasikmalaya Regency. The method used in this study is a survey method with multiple linear regression correlation techniques and a sample size of 100 students. Based on the results of the hypothesis and data analysis, it can be concluded as follows: 1) There is a significant effect of conceptual understanding and learning motivation together on the science learning achievement of junior high school students in Sodonghilir District, Tasikmalaya Regency. This is evidenced by the Sig value = 0.000 <0.05 and Fcount = 35.989, 2). There is a significant influence of conceptual understanding on students' science learning achievement at Public Junior High Schools in Sodonghilir District, Tasikmalaya Regency. This is evidenced by the Sig value = 0.000 <0.05 and tcount = 4.156, 3). There is a significant influence of learning motivation on students' science learning achievement at Public Junior High Schools in Sodonghilir District, Tasikmalaya Regency. This is evidenced by the Sig value = 0.000 <0.05 and tcount = 4.864.